Konzorcijsko delovanje in sredstva za mednarodno znanstveno literaturo in baze podatkov v Sloveniji za leto 2010 - Mandelj, Tilen (Knjižnica, 2010)
One of the basic ways of scientific communication is publishing in scientific journals which play a key role in the evaluation of scientific excellence and as such represent an indispensable part of scientific infrastructure. Their relevance is reflected in the high use rate. The article presents experiences in consortium purchases of scientific journals in the Republic of Slovenia within the management of the Central Technological Library at the University of Ljubljana (CTK). In 2009, the number of successful full-text article requests amounted to 829,576 EUR, an increase of 33% compared to the year 2008 and 178% more requests than in 2006. The Slovenian Research Agency (SRA) supports libraries in consortium purchasing and is responsible for co-financing foreign scientific library resources in the Republic of Slovenia. In 2009, the amount of EUR 3,520,000 was given to libraries, of which the consortium received EUR 1,421,458, an increase of 419% compared to the previous year. Consequently eight new members joined the consortium in 2010, now involving 22 institutions. The article also presents the benefits of additional financial means given to the consortium.
Keywords: knjižnični konzorciji; znanstvene revije; nabava; purchasing; Slovenia; Slovenija